2018
DOI: 10.1111/sltb.12454
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Suicide Attempts for Racial and Ethnic Groups of Patients During Routine Clinical Care

Abstract: The aim of this study was to examine variation in suicide ideation and its relationship to risk of suicide attempt in the subsequent 90 days by race and ethnicity. Participants were adults who completed the Patient Health Questionnaire depression module (PHQ9) during an outpatient encounter between January 10, 2010, and December 12, 2012 (N = 509,945 patients; N = 1,228,308 completed PHQ9). Data came from the Virtual Data Warehouse from four health care systems in the Mental Health Research Network. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…(e.g., Granillo, 2012;Keum et al, 2018;Merz et al, 2011;Morehead, 2012), we limited our analyses to comparing American Indian adults with the dominant Caucasian American group. Moreover, while the PHQ-9 total score measures depression symptom severity (Kroenke et al, 2001), item 9 is predictive of suicidality (Coleman et al, 2018;Simon et al, 2013;Simon et al, 2016). However, only a small number of individuals in this study had evidence of attempted or completed suicide in the EHR (based on ICD-9 or ICD-10 diagnosis codes).…”
Section: Limitationsmentioning
confidence: 84%
See 1 more Smart Citation
“…(e.g., Granillo, 2012;Keum et al, 2018;Merz et al, 2011;Morehead, 2012), we limited our analyses to comparing American Indian adults with the dominant Caucasian American group. Moreover, while the PHQ-9 total score measures depression symptom severity (Kroenke et al, 2001), item 9 is predictive of suicidality (Coleman et al, 2018;Simon et al, 2013;Simon et al, 2016). However, only a small number of individuals in this study had evidence of attempted or completed suicide in the EHR (based on ICD-9 or ICD-10 diagnosis codes).…”
Section: Limitationsmentioning
confidence: 84%
“…Lastly, item 9 loaded lower than other PHQ-9 items regardless of the factor model or racial group. Recent research has shown the predictive utility of item 9 in assessing suicidality (Coleman et al, 2018;Simon et al, 2013;Simon et al, 2016). Future research could consider developing additional questions related to suicidality for the PHQ-9 and creating a separate factor that assesses suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, participants were all of Korean descent from a single tertiary hospital, limiting this study's generalizability to other populations or ethnic groups. Cultural, lifestyle, and ethnic differences could play a role in the risk factor for SSA in the old age group ( 54 ). Future studies should also consider the heterogeneity of the study participants, including recruiting sites and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Suicides were preventable, and there were more than 20 attempts per suicide [3] . The Distress Assessment and Response Tool has been used to identify suicidal ideation in patients with cancer [36] , and item 9 of the Patient Health Questionnaire depression module (PHQ9) was also a strong predictor of suicide attempts and suicide deaths in patients [37] . It was necessary to select patients whose age at diagnosis was less than 14 or more than 60 out when considering the suicide risk of patients with malignant bone tumors.…”
Section: Discussionmentioning
confidence: 99%